2009
DOI: 10.1002/ca.20888
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic position of the asterion in Kenyans for posterolateral surgical approaches to cranial cavity

Abstract: The asterion, defined as the junction between lambdoid, parietomastoid, and occipitomastoid sutures, has been used as a landmark in posterolateral approaches to the posterior fossa. Its reliability however has been put into question due to its population-specific variability in position, using external palpable landmarks and its relation to the transverse-sigmoid sinus complex. This study aimed at determining the anatomic position of the asterion in a Kenyan population. Measurements from the asterion to the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 12 publications
1
43
0
Order By: Relevance
“…In previous studies ıt has been found that the asterion is mostly located superficial to the STJ in adults (Gharabaghi et al, 2008a;Mwachaka et al;Srijit et al;Ribas et al).…”
Section: Asterion (A) Henle's Spine (Hs) External Occipital Protubementioning
confidence: 92%
See 3 more Smart Citations
“…In previous studies ıt has been found that the asterion is mostly located superficial to the STJ in adults (Gharabaghi et al, 2008a;Mwachaka et al;Srijit et al;Ribas et al).…”
Section: Asterion (A) Henle's Spine (Hs) External Occipital Protubementioning
confidence: 92%
“…Some authors reported that reliability of using asterion as a surface landmark remained debatable. However its location was indespensible to identify the STJ for a successful posterior approach surgery in cranial fossa Gharabaghi et al, 2008a;De Paiva & Segre;Mwachaka et al).…”
Section: Asterion (A) Henle's Spine (Hs) External Occipital Protubementioning
confidence: 99%
See 2 more Smart Citations
“…The position of the asterion was determined as being over the transverse-sigmoid sinus complex, above it (over supratentorial dura) or below it (over posterior fossa dura) (Figure 2A-C). Data obtained were analysed using the statistical package software (SPSS version 12.0, SPSS) (8). Side and gender differences were assessed by Student's t test.…”
Section: █ Introductionmentioning
confidence: 99%